2018
DOI: 10.1016/j.chest.2017.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Pulmonary Nodule Location During Electromagnetic Bronchoscopy With Predicted Location on the Basis of Two Virtual Airway Maps at Different Phases of Respiration

Abstract: Predicted 3D nodule location using an EXP scan for ENB is significantly closer to actual nodule location when compared with an INSP scan, but whether this leads to increased yields needs to be determined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 24 publications
0
12
0
Order By: Relevance
“…Whereas most peripheral bronchoscopy data report a navigational yield of about 90% or even higher, the diagnostic yield remains closer to 70%. 2,4,5,8,12 This gap likely has more than one explanation. The inability of our current biopsy tools to obtain proper samples can be one.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Whereas most peripheral bronchoscopy data report a navigational yield of about 90% or even higher, the diagnostic yield remains closer to 70%. 2,4,5,8,12 This gap likely has more than one explanation. The inability of our current biopsy tools to obtain proper samples can be one.…”
Section: Discussionmentioning
confidence: 99%
“…The concept of the moving target and its excursion throughout the respiratory phases has been well described. 8,12 Adding to these barriers to accurate navigation, we now hypothesize that, when performed under general anesthesia, the development of atelectasis also plays an important role in CT-body divergence. Atelectasis can either shorten the airways, or pull them and the targets in different directions, away from their original location on the planning CT scan.…”
Section: Discussionmentioning
confidence: 99%
“…This system uses an algorithm to pair inspiratory and expiratory CT scans with the respiratory cycle in order to compensate for respiratory variation, in an attempt to mitigate CT-to-body divergence. One study found that the inspiratory/expiratory CT scan protocol with periprocedural respiratory motion sensing and gating provides better nodule location accuracy than inspiratory-only CT scans (21). However, while intuitively appealing, limited data are currently available on this system, with reported diagnostic yields of 33% (27), 90% (28), and 83% (3) in three small, single-center studies.…”
Section: Lung Volume Differencesmentioning
confidence: 99%
“…Firstly, the motion of pulmonary lesions during the respiratory cycle, especially when they are located in the lower lobes: the acquisition of inspiratory and expiratory CT sequences allows a better virtual reconstruction of the endobronchial pathway to the lesion. Secondly, the acquisition of CT on the same day of the bronchoscopic procedure could reveal last-minute variations in the characteristics of lesions [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…A pre-procedure CT collects images during the inspiratory and expiratory phases and then, during the airway inspection, the sensor probe collects 3D points reconstructing both the lumen registration map and the pathway to the target lesion. Pulmonary nodules location was demonstrated to be closer on expiratory phase acquisition images than inspiratory ones, suggesting a coordination during expiratory phases of sampling procedure [ 21 ]. Moreover, this technology incorporates the electromagnetic guidance system to perform a transthoracic needle aspiration (TTNA) sampling by using the same CT images.…”
Section: Introductionmentioning
confidence: 99%